Clark gateway Luzon-Clark International Hub - Macam, Bonnie Petit M. (College of Architecture, University of the Philippines Diliman, 2018)
This Comprehensive design project is an intermodal transportation center that functions as an interchange for passengers going to Central or Northern Luzon and promotes the historic and tourist attractions of Clark Freeport Zone while accommodating and consolidating future and existing modes of transportation. The project was realized through the formulation of the agenda from the issues and potentials of the chosen macro site. Clark Freeport Zone, which were gathered and related to one another, generating the three main themes of the agenda: transportation, tourism, and community building. The goal of the project was to function as the main gateway of Clark Freeport Zone while ensuring the preservation of existing green spaces within the site, with additional problems such as the limited site and the multiple different transit systems to be integrated with one another, along with the incorporating ease of wayfinding through the building design. The final structure is a five-level structure with the different transit systems on different levels, with community and tourism spaces integrated into them. An open design that highlights the different circulations of transit systems and users ensures the visibility of movement within the building as a form of wayfinding.